Hope Abjuring Hope: On the Place of Utopia in Realist Political Theory. (October 2018) - Thaler, Mathias
This essay reconstructs the place of utopia in realist political theory, by examining the ways in which the literary genre of critical utopias can productively unsettle ongoing discussions about "how to do political theory." I start by analyzing two prominent accounts of the relationship between realism and utopia: "real utopia" (Erik Olin Wright et al.) and "dystopic liberalism" (Judith Shklar et al.). Elaborating on Raymond Geuss's recent reflections, the essay then claims that an engagement with literature can shift the focus of these accounts. Utopian fiction, I maintain, is useful for comprehending what is (thus enhancing our understanding of the world) and for contemplating what might be (thus nurturing the hope for a better future). Ursula K. Le Guin's novel The Dispossessed deploys this double function in an exemplary fashion: through her dynamic and open-ended portrayal of an Anarchist community, Le Guin succeeds in imagining a utopia that negates the status quo, without striving to construct a perfect society. The book's radical, yet ambiguous, narrative hence reveals a strategy for locating utopia within realist political theory that moves beyond the positions dominating the current debate. Reading The Dispossessed ultimately demonstrates that realism without utopia is status quo–affirming, while utopia without realism is wishful thinking.